2012
DOI: 10.1155/2012/384685
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Platelets and the Immune System: Old Systems with New Discoveries

Abstract: Platelets are small anucleate cells circulating in the blood. It has been recognized for more than 100 years that platelet adhesion and aggregation at the site of vascular injury are critical events in hemostasis and thrombosis; however, recent studies demonstrated that, in addition to these classic roles, platelets also have important functions in inflammation and the immune response. Platelets contain many proinflammatory molecules and cytokines (e.g., P-selectin, CD40L, IL-1β, etc.), which support leukocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 192 publications
(233 reference statements)
2
104
0
1
Order By: Relevance
“…This phenomenon validates a remarkable increase in our understanding regarding the roles of platelets in haemostasis, thrombosis and wound repair (13). Correspondingly, current evidence has shown that platelets are entangled in many other physiological and pathological processes beyond haemostasis and thrombosis such immuno-thrombosis, the development of atherosclerosis, lymphatic vessel enlargement, angiogenesis and tumour metastasis (14)(15)(16).…”
Section: Development and Platelet Formationsupporting
confidence: 61%
“…This phenomenon validates a remarkable increase in our understanding regarding the roles of platelets in haemostasis, thrombosis and wound repair (13). Correspondingly, current evidence has shown that platelets are entangled in many other physiological and pathological processes beyond haemostasis and thrombosis such immuno-thrombosis, the development of atherosclerosis, lymphatic vessel enlargement, angiogenesis and tumour metastasis (14)(15)(16).…”
Section: Development and Platelet Formationsupporting
confidence: 61%
“…2 They are widely expressed by immune cells and other nonimmune cells, such as endothelial cells, epithelial cells, fibroblasts, cardiomyocytes, and platelets. 1,2,4 Viral infections are mainly detected by endosomal TLRs that recognize nucleic acid ligands from the virus. 2,5 TLR3 recognizes the dsRNA of dsRNA viruses and dsRNA that is made during replication of ssRNA viruses.…”
Section: The Innate Immune Response To Virus Infectionmentioning
confidence: 99%
“…Recent studies show that platelets have many functions beyond physiologic or pathologic thrombus formation. They play a role in inflammation, 5,6 are effectors of injury in a variety of pulmonary disorders and syndromes, 7 facilitate tissue repair, 8 and act in the growth and development of metastases of various cancers. 9 It has been well established that platelets are vital for liver regeneration after a partial liver resection in animals.…”
Section: Evidence For a Stimulatory Role Of Platelets In Liver Regenementioning
confidence: 99%